Health Care and Genesee County, New York: Economic Implications of Reduced Hospital Services - Nelson L. Bills; David Kay (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2002)
Changes in health care delivery and financing, along with shifting demographics, are reinventing health care institutions and market relationships. Many communities are struggling to provide health care services in ways that protect community economic interests and the health needs of local people. Local business interests, hospitals, and doctors in many communities are increasingly concerned about the capacity to provide quality products and services, while remaining competitive with providers in neighboring areas. This study assesses the contribution health care providers make to the Genesee County economy. Other noneconomic contributions of this sector to local well-being are acknowledged here, but are not analyzed as part of the study.
Keywords: 330